solve this equation for x

Apr 2010
2
0
How do you do this?

solve for x:

ax = bx - c

Thank you.
-r
 
Nov 2009
517
130
Big Red, NY
\(\displaystyle ax = bx - c\)

\(\displaystyle \implies ax- bx = -c\)

\(\displaystyle \implies x(a- b) = -c\)

\(\displaystyle \implies \boxed{x=-\frac{c}{a-b}}\)
 
Last edited:
May 2010
5
1
solve for x:

ax = bx - c

solution: ax - bx = c
(a -b)x = c
x = c/(a - b)
 
May 2010
1
0
correct solution

This is the correct solution:
\(\displaystyle

ax = bx - c
\)
\(\displaystyle

\implies ax- bx =-c
\)
\(\displaystyle

\implies x(a- b) =-c
\)
\(\displaystyle

\implies \boxed{x=-\frac{c}{a-b}}
\)
 
Apr 2010
2
0
thank you for helping

it seems so easy when you see the solution, but not so easy when your making holes in the wall with your forehead.(Coffee)
 
Dec 2009
3,120
1,342
it seems so easy when you see the solution, but not so easy when your making holes in the wall with your forehead.(Coffee)
To protect the wall from your forehead, you need to know how to think it through.

Solve for x means we are being asked to write x=?

What we are given contains x in 2 places, on either side of the equal sign.
When both sides are equal we can perform the exact same operation to both sides.

For instance 5=5

If we subtract 3 from both sides we'll have 5-3=5-3 which is 2=2

The sides may not be what they were originally but they are still equal.

Hence

\(\displaystyle ax=bx-c\)

has x on both sides.
To get the x's on the same side, subtract bx from both sides,
the two sides will still be equal...

\(\displaystyle ax-bx=bx-bx-c\)

\(\displaystyle bx-bx=0\)

therefore we have

\(\displaystyle ax-bx=-c\)

If you have 5 boxes of apples, 20 apples per box
and you give 3 boxes to your sister, how many apples will you have ?

\(\displaystyle 5(20)-3(20)=(5-3)(20)\)

You can calculate 100-60=40 or 2(20)
You get the same answer.

Hence we get x in one place by factorising as above.

\(\displaystyle ax-bx=-c\)

\(\displaystyle x(a-b)=-c\)

This is "x multiplied by both a and -b".

To move the (a-b) away from the x, to leave x standing alone,
we divide both sides by (a-b), just as

\(\displaystyle 3x=6\ \Rightarrow\ \frac{3x}{3}=\frac{6}{3}\)

\(\displaystyle \frac{3}{3}x=\frac{6}{3}\)

As \(\displaystyle \frac{3}{3}=1\)

this is

\(\displaystyle x=2\)

Hence

\(\displaystyle \frac{x(a-b)}{(a-b)}=-\frac{c}{(a-b)}\)

\(\displaystyle \frac{(a-b)}{(a-b)}=1\)

\(\displaystyle x=-\frac{c}{a-b}=\frac{c}{b-a}\)
 
Last edited: